Technologies for smallholder irrigation appropriate for whom: promoters or beneficiaries? - Malik, Ravinder Paul Singh; Fraiture, Charlotte de; Ray, D. (2013)
Fifteen years after the successful introduction of treadle pumps for small farm irrigation in the North Bengal region of India, the socio-economic and technological landscape has changed dramatically. However, donors have continued to support treadle pump programs. Revisiting the factors that contributed to its initial success, the authors in this paper examine whether the use of treadle pumps continues to be an appropriate technology for smallholder irrigation. The results suggest that treadle pumps, when introduced during the mid-1990s, were successful because of a near technological vacuum at that time. Over the years, with the advent of small affordable diesel engines, motorized pumps have become widely available and a large rental market for water and pumping equipment has emerged. The farmers started abandoning the treadle pumps. Growing labor scarcity, rising labor wages, and increasing concerns over drudgery also dissuaded farmers from using the labor-intensive treadle pumps. The study reaffirms that the adoption of a technology is a dynamic process and that a technology that was appropriate at one point in time will not necessarily remain so at other times. It underlines the need for regularly revisiting technology choices and independent monitoring to understand better the changing landscapes of smallholder irrigation. This will ensure that the technologies desired most by beneficiariesï¿½not just by promotersï¿½get the support and promotional backing of the donors and governments for effective poverty reduction.